IMPROVING PATIENT'S SATISFACTION USING LEAN HEALTHCARE AND KANO MODEL - SEENI MOHAMED, MUHAMMAD ANWAR IBRAHIM (IRC, 2017)
Patient’s satisfaction in the hospitals is one of the most important factor in determining the successfulness of the treatment given. In increasing the patient’s satisfaction particularly in public hospitals, the lean healthcare concept and Kano model were used to address this issue. Patient’s satisfaction is always associated with the whole treatment experience the moment the enter the medical facility to the time they are discharged. The objectives for this study are to identify critical factors in improving patient’s satisfaction in the Emergency Department and Medical Ward of a public hospital. The lean methodology was used regarding conducting a time study is done to identify the process time in the Emergency Department of the whole treatment experience and to find ways in improving the efficiency by applying the lean process. The concept of Kano model was applied by developing a questionnaire in determining the features that could increase the patient satisfaction in the Emergency Department and the Medical Ward. The philosophy of kaizen methodology particularly brainstorming was used in encouraging all staff of the Hospital Raja Permaisuri Bainun to contribute ideas and suggestions for improvement. Based on the time study conducted it shows that the overall process time is within the target set by the government. The survey conducted shows three main “WOW” factors contributing to patient satisfaction. For both Emergency Department and Medical Ward, the critical factor contributing to patient satisfaction is Patient Communication. For example, doctors and hospital staff should constantly update relatives regarding the patient condition. Second, for Emergency Department, Wi-Fi Facilities should be provided. Third, for Medical Ward, more facilities such as sleeping chairs and wheelchairs should be provided. Hence, to improve the patient’s satisfaction, the hospital management must address the three factors contributing to the patient satisfaction.